Question
\( 3(x+2)=3 x+6 \) \( 3 x+2 x=x^{2}(3+2) \) \( 3 x+2=3(x+2) \) \( -3(2+x)=-6 x-3 \) Which pair shows equivalent expressions? 3
Ask by Bright Moreno. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
The first pair \( 3(x + 2) = 3x + 6 \) has equivalent expressions.
Solution
Let's analyze each of the given equations to determine which pair consists of equivalent expressions:
1. **\( 3(x + 2) = 3x + 6 \)**
- **Left Side (LS):** \( 3(x + 2) \)
- **Right Side (RS):** \( 3x + 6 \)
- **Verification:** Distributing the 3 on the left side:
\[
3(x + 2) = 3x + 6
\]
This shows that both sides are indeed equivalent.
2. **\( 3x + 2x = x^{2}(3 + 2) \)**
- **Left Side (LS):** \( 3x + 2x = 5x \)
- **Right Side (RS):** \( x^{2}(3 + 2) = 5x^2 \)
- **Verification:** The left side simplifies to \( 5x \) and the right side to \( 5x^2 \). These are **not** equivalent unless \( x = 0 \) or \( x = 1 \).
3. **\( 3x + 2 = 3(x + 2) \)**
- **Left Side (LS):** \( 3x + 2 \)
- **Right Side (RS):** \( 3x + 6 \)
- **Verification:** Subtracting \( 3x \) from both sides:
\[
2 = 6
\]
This is a false statement, so the expressions are **not** equivalent.
4. **\( -3(2 + x) = -6x - 3 \)**
- **Left Side (LS):** \( -3(2 + x) = -6 - 3x \)
- **Right Side (RS):** \( -6x - 3 \)
- **Verification:** Comparing both sides:
\[
-6 - 3x \quad \text{vs.} \quad -6x - 3
\]
These are **not** equivalent.
**Conclusion:**
Only the **first pair** \( 3(x + 2) = 3x + 6 \) consists of equivalent expressions.
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
The first pair, \( 3(x+2)=3x+6 \), shows equivalent expressions because when you distribute the 3 on the left side, you indeed get \( 3x + 6 \), confirming both sides are equal. The second pair, \( 3x + 2x = x^{2}(3 + 2) \), does not show equivalent expressions as the left side simplifies to \( 5x \), while the right side simplifies to \( 5x^{2} \), which are not equal.